Evaluating and predicting impacts of Australian redclaw crayfish Cherax quadricarinatus and Louisiana red swamp crayfish Procambarus clarkii invasions - Madzivanzira, Takudzwa Comfort (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Freshwater crayfish have become one of the most widely introduced freshwater taxa globally. Crayfish introductions have not spared the African continent, which, apart from Madagascar, is naturally devoid of native freshwater crayfish. These introductions are of concern because invasive crayfish have generally been shown to cause strong impacts on recipient ecosystems outside Africa. This study therefore set out to compile up-to-date information regarding crayfish introductions in Africa, their pathways and distributions and to improve our understanding of the nature and magnitude of their environmental impacts. A systematic review revealed that nine crayfish species have been introduced into the continent with five of those, Astacus astacus, Cherax quadricarinatus, Faxonius limosus, Procambarus clarkii and Procambarus virginalis, having established naturalised populations in fourteen African countries (Chapter 2). The main driver of these crayfish introductions was to provide socio-economic benefits but there is limited evidence of success. The thesis further documents attempts made to address crayfish knowledge gaps in Africa, including standardisation of C. quadricarinatus sampling gear (Chapter 3), determination of the distribution of C. quadricarinatus in the recently invaded Upper Zambezi Basin (Chapter 4), and predicting ecological and socioeconomic impacts of two crayfish species that are spreading rapidly in Southern Africa, namely, C. quadricarinatus and P. clarkii (Chapters 5 "“ 8). To standardise C. quadricarinatus sampling methods in Africa, two methods used in Southern Africa were compared and the PromarÂ® collapsible trap baited with dry pellets was recommended as the best approach for C. quadricarinatus abundance studies due to the high catch per unit effort (CPUE), probability of capture and the suitability of dry dog food as a standard bait. This standard approach was used for crayfish surveys in the Zambezi Basin to comprehensively determine the spread and establishment of C. quadricarinatus across the basin. The establishment of C. quadricarinatus in the Barotse Floodplain, Upper Zambezi Floodplains freshwater ecoregion was confirmed. Although the probability of capture and catch per unit effort (CPUE) of C. quadricarinatus in the Barotse floodplain were similar to that of older invasions in the basin (Lake Kariba and Kafue River), morphometric differences among C. quadricarinatus populations sampled from these invaded regions were detected. Although crayfish were not detected in other regions, for example, the Okavango Floodplains ecoregions, C. quadricarinatus have the potential to spread at a downstream and upstream rate of 49 and 12 kmÂ·year-1, impacting native biota therein. To evaluate the potential for ecological impacts, the consumer-resource dynamics of C. quadricarinatus and P. clarkii were described in comparison to a native trophic analogue, the freshwater crab of the Potamonautes genus, preying on various native taxa ubiquitous to African aquatic and terrestrial ecosystems. The use of functional response (FR) and consumption experiments in this study showed the potential impacts of the two crayfish species on native resources and on resources that support livelihoods in invaded ecosystems. This in most cases was a result of their high attack parameter, which also resulted in high functional responses ratios (FRRs) compared to native crabs. The crayfish FR, FRRs and consumption rates were mostly enhanced under the high temperature treatments. The FRs and consumption results were then combined with the field biomasses of crayfish and crabs to calculate the relative impact potential (RIP) to successfully predict the degree of impact caused by crayfish species relative to crabs. Crayfish species consistently displayed RIP scores > 1 relative to the native crab irrespective of region, which were higher for the summer than the winter season, suggesting greater impact of the invaders compared to the native species. This study further estimated the socioeconomic losses due to catch spoilage by C. quadricarinatus which are up to 1500 t per year in the invaded Kafue River Basin, which translates to an annual income loss of US$ 2 million. Information provided in this study is vital for conservation management and to compel policymakers to develop appropriate conservation management tools within regulatory frameworks, which could stop or minimise the spread of crayfish species and protect Africa from further losing aquatic biodiversity.
Keywords: Cherax -- Africa; Procambarus clarkii -- Africa; Freshwater crabs -- Africa; Crayfish -- Zambezi River; Crayfish -- Food -- Zambezi River; Aquatic biodiversity -- Africa; Conservation biology -- Zambezi River; Fishing -- Catch effort -- Africa; Introduced freshwater organisms -- Africa; Fish populations -- Africa; Functional response (FR)